Elemental Impurities in Pediatric Calcium Carbonate Preparations-High Throughput Quantification and Risk Assessment - Xiao, Chaoqiang; Zhu, Li; Zhang, Xia; Gao, Rumeng; He, Shuwang; Lv, Zhihua; Hu, Changqin (Frontiers in Chemistry, 2021)
Calcium carbonate which is extracted from the earth in combination with other minerals, is largely used in preparations for pediatric supplements. Thus, it is very urgent to assess the safety of chronic exposure to elements that may be present in trace amounts and development related method to control the trace elements. In the present study, we developed high throughput ICP-MS method for the quantitative determination of 62 elemental impurities in high matric calcium carbonate samples and validated according to USP <233>. Calcium carbonate preparations which state clearly used for child (including neonates, infants, toddlers and children) from 9 manufactures and two types of raw materials (light calcium carbonate and ground calcium carbonate) were investigated in terms of the content and variability of 62 elemental impurities. According to the results, ground calcium carbonate was slightly superior to light calcium carbonate concerning element impurities. Risk assessment showed the elemental impurities in CaCO3 preparations are not only derived from the raw materials but also from the preparation process. The contents of Pb, Na, Fe and other elements in some products posing potential risks for young children. These results indicate that it is necessary to establish a modern instrumental analysis method to replace the tranditional method to evaluate and control elemental impurities in CaCO3 preparations.